Enhancing Listening Comprehension through Youtube Videos for Non-English Major Students - Delis Meta Tiana; Ary Iswanto Wibowo; Jimmi Jimmi; Rina Lestari (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2023)
The goal of this study is to enhance students' listening comprehension by using YouTube videos. This study employed classroom action research Kemmis and Taggart’s design as its methodology. There were thirty- five of non-English major students in the subject. The findings demonstrate a significant improvement in students' listening comprehension. After the teaching and learning process using YouTube videos, it reveals that the students' mean score in cycle 1 was 68.3, with 68.57% passing the minimum standard score. It continued to cycle 2 with a mean score of 71.0 and a passing percentage of 85.71%, indicating a significant improvement in listening test results. In cycle 3, students' mean score was 84.2, and 94.29% passed the minimum standard score. Hence, the implementation of YouTube videos as a learning media can help students to enhance their listening comprehension. It is proven by the improvement of students’ mean score and their learning performance in each cycle.